GHANAIAN CLAY PRACTICES: A RETHINKING - Samuel Nortey; Edwin K. Bodjawah (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2022)
This paper discusses Ghanaian clay practices and how their histories and some practices limit their clay discourse, creating a disconnect from ecologies of practice. Western contemporary and academic ceramics communities acknowledge the present and historic lack of diversity and inclusion of Global south indigenous practice, a condition that has been constant since there has been a conception of “contemporary ceramics”. Documentation of art has been largely the exclusive province of art historians, yet, Ghana never had art history has a major in any Ghanaian university including Achimota School that was set up by the colonial government. There are several ceramic material sites but no processing industries for creating products. This paper signals a rethinking of forms, economic exchange, materiality and recommends that it is expedient to expand Ghanaian clay practice discourse in all forms to connect to the ecologies of practice by forward-thinking, looking at the indigenous ceramic medium outside the pigeonhole, and pushing the boundaries of conventional Ghanaian ceramics.